An Overview of Body Mass Index and Helminthic Infections Among Primary School Children - Sabinus Kedang; Wihelmus Olin (GLOBAL HEALTH SCIENCE GROUP, 2026)
Helminthic infections in primary school children can contribute to nutritional problems. One commonly used indicator of children's nutritional status is Body Mass Index (BMI). This study aimed to describe the Body Mass Index (BMI) and the prevalence of intestinal helminth infections among primary school children in Amanuban Barat Subdistrict. This study was conducted in Amanuban Barat Subdistrict, South Central Timor Regency (TTS), in 2023. The research employed a quantitative descriptive design to explore the BMI status and the incidence of intestinal helminth infections among primary school children. A total of 80 students were selected using purposive sampling. Data collection involved stool examination, anthropometric measurements (height and weight), BMI calculation, and descriptive data analysis. The results showed that stool examination revealed 83% negative and 17% positive for helminth infections. The average BMI among students was 15.37, with a maximum of 20.27, a minimum of 12.77, and a standard deviation of 1.47. The average nutritional status was categorized as severely underweight. Among the 80 students, 42 underwent stool examination, and 12 were found to be positive for helminth infections. Of those 12 infected students, 10 (83.3%) had a BMI indicating severely underweight, and 2 (16.7%) were underweight. The average BMI of primary school children in this study indicated a severely underweight nutritional status. There were 12 students infected with helminths, with the majority of them showing signs of poor nutritional status.